The Influence of Product Quality, Perceived Price and Service Quality on Customer Satisfaction at The Terrace Restaurant - Kharismah Salsabilla; Hariadi Hadisuwarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of product quality, price perception, and service quality on customer satisfaction at The Terrace Restaurant. Data was collected through a questionnaire filled out by 100 respondents who are customers of the restaurant. Linear regression analysis was used to examine the relationship between these variables. The results showed that product quality and price perceptions had a significant positive effect on customer satisfaction, while service quality had a significant negative effect on customer satisfaction. Good product quality, appropriate price perceptions, and good service will increase customer satisfaction at The Terrace Restaurant. This finding has important implications for restaurant management in improving product quality, managing price perceptions, and improving service quality in order to achieve higher customer satisfaction.